Kesultanan Aceh di Mata Turki Utsmani Abad XIX: Kajian Atas Naskah Diplomatik Abdurrahman Az-Zahir - Azzahra, Humaira (Masyarakat Pernaskahan Nusantara, 2023)
The relationship between the Aceh Sultanate and Ottoman in the 19th century was motivated by European colonialization. In a threatened state of sovereignty, the Aceh Sultanate mobilized international forces by sending envoys to its allies to establish diplomacy, one of which was to Ottoman. In 1873, Abdurrahman az-Zahir was sent to Ottoman Turkey as a representative of the Aceh Sultanate to ask for support. There is a letter written by him regarding Aceh's request to become a vassal state of Ottoman. This study examines the contents of Abdurrahman az-Zahir's letter as part of the diplomatic letters of the Aceh Sultanate to Ottoman in the 19th century. The letter is currently stored at the Turkish Archives with the code BOA, A. MKT.MHM. 457/55 and no manuscript copy was found. The aims of this study is to reveal the status of the Aceh Sultanate in its relationship with Ottoman in the 19th century. The result of the study shows that the relationship between the Aceh Sultanate and Ottoman in that century was a relationship between two equal countries. The Aceh Sultanate was not a vassal state of Ottoman. === Hubungan Kesultanan Aceh dengan Turki Utsmani pada abad 19 dilatarbelakangi oleh kolonialisasi yang digencarkan Eropa. Dalam kondisi kedaulatan yang terancam, Kesultanan Aceh menggalang kekuatan internasional dengan cara mengirim utusan ke negara-negara sahabat untuk menjalin diplomasi, salah satunya ke Turki Utsmani. Pada tahun 1873, Abdurrahman az-Zahir diutus ke Turki Utsmani sebagai perwakilan Kesultanan Aceh untuk meminta sokongan. Terdapat sepucuk surat yang ditulis olehnya berkenaan dengan permintaan Aceh untuk menjadi negara vasal Turki Utsmani. Penelitian ini mengkaji isi naskah surat Abdurrahman az-Zahir sebagai bagian dari surat diplomatik Kesultanan Aceh ke Turki Utsmani pada abad 19. Surat tersebut kinitersimpan di Badan Arsip Turki dengan kode BOA, A. MKT.MHM. 457/55 dan tidak ditemukan adanya salinan naskah. Tujuan penelitian ini adalah untuk mengungkap relasi Kesultanan Aceh dengan Turki Utsmani pada abad 19. Hasil dari penelitian menunjukkan bahwa hubungan antara Kesultanan Aceh dengan Turki Utsmani pada abad tersebut merupakan hubungan persahabatan dua negara yang setara. Kesultanan Aceh bukan merupakan negara vasal (pengikut) dari Turki Utsmani.